2017
DOI: 10.1098/rsos.160426
|View full text |Cite|
|
Sign up to set email alerts
|

A Bayesian bird's eye view of ‘Replications of important results in social psychology’

Abstract: We applied three Bayesian methods to reanalyse the preregistered contributions to the Social Psychology special issue ‘Replications of Important Results in Social Psychology’ (Nosek & Lakens. 2014 Registered reports: a method to increase the credibility of published results. Soc. Psychol. 45, 137–141. (doi:10.1027/1864-9335/a00019210.1027/1864-9335/a000192)). First, individual-experiment Bayesian parameter estimation revealed that for directed effect size measures, only three out of 44 central 95% credible int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 74 publications
0
48
0
Order By: Relevance
“…Validity of research methods is a timely topic. Large‐scale replication projects in psychology and biomedicine have revealed that a disturbingly low percentage of top journal studies can be successfully replicated (Marsman et al, ; Open Science Collaboration, ). Our study may offer some interesting opportunities for so‐called quasi‐replications where the robustness of previous findings are tested against different methods (Bettis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Validity of research methods is a timely topic. Large‐scale replication projects in psychology and biomedicine have revealed that a disturbingly low percentage of top journal studies can be successfully replicated (Marsman et al, ; Open Science Collaboration, ). Our study may offer some interesting opportunities for so‐called quasi‐replications where the robustness of previous findings are tested against different methods (Bettis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a key question in psychology and neuroscience has concerned the credibility of reported findings (Open Science, 2015;Button et al, 2013;Pashler et al, 2012;Munafo et al, 2017;Vazire, 2018) with estimates of replicability ranging between 25 and 75% (Nosek & Lakens, 2014;Matzke et al, 2015;Marsman et al, 2017;Camerer et al, 2018). Studies that integrate experimental and differential approaches are rare in general, and in the context of imitation control, prior studies have typically used small sample sizes (Ainley et al, 2014;Chartrand & Bargh, 1999;Obhi et al, 2013;Santiesteban et al, 2015).…”
Section: Are Individual Differences In Interference Control Robust Anmentioning
confidence: 99%
“…For instance, the Open Science Collaboration (2015) showed that out of 100 replication studies, only 39 supported the conclusions that were drawn in the original article (but see Etz and Vandekerckhove 2016; see also Camerer et al 2018). Similarly disappointing results were obtained for specific subfields (e.g., Marsman et al 2017;Klein et al 2018;Nosek and Lakens 2014), and for particular effects (e.g., Eerland et al 2016;Harris et al 2013;Matzke et al 2015;Meyer et al 2015;de Molière and Harris 2016;Shanks et al 2013;Unsworth et al 2015;Wagenmakers et al 2016, among many others).…”
mentioning
confidence: 95%